2014
DOI: 10.1055/s-0034-1375181
|View full text |Cite
|
Sign up to set email alerts
|

Practice of Embryo Transfer: Recommendations During and After

Abstract: Many patient and embryo factors influence the outcome of assisted reproductive technology (ART) treatment. The predictors for a successful ART cycle include female age, ovarian reserve, embryo quality, endometrial receptivity, and embryo transfer (ET) technique. ET, the final step of ART, has recently been noted as a crucial step affecting ART success. Variables affecting pregnancy rates following ET include ultrasound guidance, ease of ET transfer, catheter type, transfer and catheter-loading technique, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 70 publications
(68 reference statements)
1
3
1
Order By: Relevance
“… 16 Other causes include traumatic contact with the cervix or the endometrium, resulting in bleeding. 17 Our findings supported the results of prior studies. 16 , 18 , 19 Thus, it is recommended to perform embryo transfer under atraumatic conditions without the presence of blood or mucus to increase the likelihood of implantation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 16 Other causes include traumatic contact with the cervix or the endometrium, resulting in bleeding. 17 Our findings supported the results of prior studies. 16 , 18 , 19 Thus, it is recommended to perform embryo transfer under atraumatic conditions without the presence of blood or mucus to increase the likelihood of implantation.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that mucus can significantly impact the outcome of assisted reproductive technology (ART) by causing mechanical obstruction of the catheter opening, resulting in embryo retention. 17,[23][24][25] In our study, however, the linear regression model showed that there was no significant association between the presence of mucus during embryo transfer and the success of IVF-ET. This observation aligns with what other studies have found.…”
Section: Discussioncontrasting
confidence: 84%
“…It has been hypothesized that blastocyst stage ET would permit the identification of embryos that could maintain their developmental process and, thus, allow the recruitment of good quality embryos with enhanced developmental ability. Therefore, it has been suggested that the blastocyst transfer at day 5 would succeed the highest pregnancy rates with the least number of embryos ( 5 , 6 , 7 ) . It is well known that growth and blastocysts at the 8-cell stage need a more complex environment, but the recent formulation of highly specialized media has permitted the preservation of blastocysts in vitro ( 8 , 9 , 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…However, a successfully implanted embryo can be found in a different area than expected for different reasons. According to Tiras & Cenksoy (2014), there is a movement of the air bubbles soon after the placement of the embryos in the uterine cavity that can influence the rates of implantation and pregnancy. The movement of the embryos towards the cervical canal may be associated with lower clinical pregnancy rates, whereas movement towards the uterine fundus may be associated with higher pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%